Asuhan Kebidanan Pada Ibu Hamil Trimester III Di PMB Hayati Wilayah Kerja Puskesmas Laboy Jaya Tahun 2022 - Alhariri, Megawati; Hastuty, Milda (Evidence Midwifery Journal, 2023)
Pregnancy is a series of processes that women experience with the meeting of an egg and sperm cell in the ovary within 280 days or 40 weeks. The purpose of this study was to determine midwifery care for pregnant women in the third trimester with frequent urination at BPM Hayati in the working area of Pukesmas Laboy Jaya in 2022. This study used a descriptive observational research design with a case study approach. The subjects of this study were pregnant women in the third trimester with frequent urination problems in PMB Hayati. Data were collected by direct interviews with pregnant women, respondent's families and physical examination as well as supporting examination, namely physical examination. On the first day until the seventh day, management is often anxious and frequent urination. Based on the pregnancy care carried out on Mrs. R obtained that frequent anxiety and frequent urination in patients is reduced